Spatial variations in forearm skin tissue dielectric constant - Mayrovitz, Harvey N.; Luis, Michelle (Skin research and technology, 2010)
Background: Tissue dielectric constant (TDC) values measured at 300 MHz via the open‐ended coaxial line reflection method depend on the effective measurement depth and the anatomical site being evaluated. Measurements on the forearm have shown that the TDC values decrease with increasing measurement depth but the spatial variability of the TDC values among forearm anatomical positions is unknown. Our goal was to characterize the extent of such spatial variations. Methods: In 30 healthy seated women (27.4±6.5 years), TDC was measured on the forearm midline and 1.2 cm medial and lateral to the midline at sites 4, 8 and 12 cm distal to the antecubital crease. Results: The midline and medial TDC values increased progressively from 4 to 8 to 12 cm sites (P<0.001), with the largest spatial gradient along the midline. At a depth of 2.5 mm, the TDC values increased from 26.3±2.8 to 27.4±3.4 to 28.4±3.7, with a maximum difference of 8.2±10.6%. For all sites, the TDC values were significantly (P<0.001) less for increasing depths. Conclusion: The findings reveal increased TDC values along the forearm from proximal to distal, most prominent at the midline and medial positions. Because many skin‐related dermatological and biophysical studies utilize the forearm as a test target, such differences may be important to consider because TDC values in part are reflective of local tissue water (LTW). Although the variation in the TDC values among sites was less than 10%, such differences are of importance when evaluating LTW changes using the TDC method in patients with arm lymphedema that is present in variable arm anatomical locations.